Modernized Hippies and Extreme Eco-Warriors - Roseline van Gogh; Michel Walrave (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
This study is the first qualitative examination of the prototype willingness model (PWM), which includes both rational and socially reactive decision-making processes, in the context of eco-friendly behaviour. In total, 33 individual face-to-face interviews were conducted with Flemish young adults between 18 and 25 years to explore how the constructs of this dual-process model manifest and interconnect in the young adults' lives in the context of eco-friendly behaviours, and which aspects should be leveraged when encouraging eco-friendly behaviour. Three prominent patterns were identified during data analysis: (1) The rational roadblocks, (2) the social stepping stone, and (3) the distant 'darker' green. Implications for (social) marketers are, among other things, to defy context-dependent attitudes of resistance (e.g. highlight applicable self-interest motives), to use social - and in particular socially reactive - levers, and to represent more diverse eco-friendly people that reflect the diversity within target audiences in behaviour change interventions and communications strategies.